Search for carbon-bearing compounds on low-albedo asteroids. Issue 1 (13th May 2022) - Hromakina, T; Barucci, M A; Belskaya, I; Fornasier, S; Merlin, F; Praet, A; Poggiali, G; Matsuoka, M
ABSTRACT: In this work, we aim to investigate the presence of absorption bands around 3.4 μm in the infrared spectra of primitive asteroids. We collected the published reflectance spectra of low-albedo asteroids from the literature and analysed the 2.4–3.8 μm region using the same techniques. From the initial data set of 92 asteroids, we restricted our analysis to 42 spectra of low-albedo asteroids with a good signal-to-noise (S/N) ratio, and we found the absorption feature around 3.4 μm in the spectra of 16 objects. For objects that are classified by the 3 μm band into the 'rounded', Ceres-like, and Europa-like groups, the depth of the 3.4 μm feature is strongly correlated with that of the 3 μm band. The majority of objects in our data set not showing the 3.4 μm absorption band have lower S/N spectra and belong to Ch or Chg classes, while asteroids with a detected 3.4 μm bands mostly belong to C, B, and also P types. Additionally, asteroids with a detected 3.4 μm band tend to have a lower albedo, redder J-K colours, and more neutral U-V colours. We observe that the analysed objects larger than ∼300 km in diameter show features due to carbon-bearing materials, which could be explained by their higher S/N ratio in our data set. Finally, we found that the distributions of asteroids showing the 3.4 μm feature appear to be shifted towards larger distances from the Sun compared to those not showing this band.